Effect of Synthesized Chemical Compounds on Seed Germination - Patil*, Vikram (Recent Research in Science and Technology, 2011)
The role of synthesized chemical compounds viz., Benzothiazolyl 3-methyl 1,2,4-1 H triazole, Benzothiazolyl 3-benzyl 1,2,4-1 H triazole, Benzothiazolyl p-nitro 1,2,4-1 H triazole, Benzothiazolyl pyridino 1,2,4-1 H triazole, 2-hydroxy 3-methoxy phenyl 4-thiazolidinone, Nickel complex with hydrazone, Gibberellins andÃ‚Â  Water. The compound, 2-hydroxy 3-methoxy phenyl 4-thiazolidinone and Nickel complex with hydrazone gave more germination as compared with standard Gibberrelic acid and water as control. Other parameters like pH, protein content using Biuret test, carbohydrate content using Anthrone method, fresh weight, dry weight, were also studied. As concentration of the compound decreases the resulting germination increases with increase in protein and carbohydrate content also.